(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
In order to account for idioms within the Chomskyan framework, Jackendoff faces two main difficulties: lexical insertion in head position only and semantic compositionality. The author thus claims that also phrases and sentences stored in the lexicon may, as such, enter the syntactic computation. Semantic interpretation, on the other hand, is described as an independent process, simultaneous with syntactic and phonological generation: the three modular representations are linked by a lexically predefined co-indexation (tripartite parallel architecture). This allows for i) internal syntactic constituents not to be linked to any conceptual constituent (non-compositional meaning, cranberry morphs); ii) elements to be compositionally computed, but with a special metaphorical import; iii) elements to have syntactic and conceptual but no phonological representation (resultatives). General postlexical rules govern phenomena such as movement, which involves also idiom-internal elements, provided they are theta-role marked.